Educational Process D A Integration Of Sciences Improvement - Inayat ELMURODOVA (Euro Asian Journal Publishing, 2024)
In this article, the improvement of the integration of subjects in the educational process, the application of content knowledge, the importance of mastering knowledge, the improvement of student knowledge in interdisciplinary teaching, the creation of problem situations, as well as the introduction of nature - society into the curricula and programs of general education schools. issues of harmonizing relations between , studying serious relations to the environment in the context of interdisciplinary integration , development of students' thinking, their worldview, behavior, general culture, environmental protection, interdisciplinary integration content, forms, teaching methods, ways, opportunities and tools, previously acquired knowledge, The state of conscious mastering of educational material by applying knowledge, skills and competencies in new situations is described using innovative educational technologies.
Keywords: integration; thinking; knowledge; improvement